Resistance gene pool to co-trimoxazole in non-susceptible Nocardia strains - Valdezate, Sylvia; Garrido, Noelia; Carrasco, Gema; Villalón, Pilar; Medina-Pascual, María J.; Saéz-Nieto, Juan A. (Frontiers in Microbiology, 2015)
The soil-borne pathogen Nocardia spp. causes severe cutaneous, pulmonary and central nervous system infections. Against them, co-trimoxazole (SXT) constitutes the mainstay of antimicrobial therapy. However, some Nocardia strains show resistance to SXT, but the underlying genetic basis is unknown. We investigated the presence of genetic resistance determinants and class 1-3 integrons in 76 SXT-resistant Nocardia strains by PCR and sequencing. By E-test, these clinical strains showed SXT MICs of ≥32:608 mg/L (ratio of 1:19 for trimethoprim: sulfamethoxazole). They belonged to 12 species, being the main representatives N. farcinica (32%), followed by N. flavorosea (6.5%), N. nova (11.8%), N. carnea (10.5%), N. transvalensis (10.5%) and Nocardia spp. (6.5%). The prevalence of resistance genes in the SXT-resistant strains was as follows: sul1 and sul2 93.4% and 78.9% respectively, dfrA(S1) 14.7%, blaTEM-1 and blaZ 2.6% and 2.6% respectively, VIM-2 1.3%, aph(3´)-IIIa 40.8%, ermA, ermB, mefA and msrD 2.6%, 77.6%, 14.4%, and 5.2% respectively, and tet(O), tet(M), and tet(L) 48.6%, 25.0% and 3.9% respectively. Detected amino acid changes in GyrA were not related to fluoroquinolone resistance, but probably linked to species polymorphism. Class 1 and 3 integrons were found in 93.42% and 56.57% strains, respectively. Class 2 integrons and sul3 genes were not detected. Other mechanisms, different than dfrA(S1), dfrD, dfrF, dfrG and dfrK, could explain the strong trimethoprim resistance shown by the other 64 strains. For first time, resistance determinants commonly found in clinically important bacteria were detected in Nocardia spp. sul1, sul2, erm(B) and tet(O) were the most prevalent in the SXT-resistant strains. The similarity in their resistome could be due to a common genetic platform, in which these determinants are co-transferred